Global Regularity of the Logarithmically Supercritical MHD System in Two-Dimensional Space (Journal of Nonlinear Modeling and Analysis, 2024)
In this paper, we study the global regularity of logarithmically supercritical MHD equations in $2$ dimensional, in which the dissipation terms are $-μΛ^{2α}u$ and $- u\mathcal{L}^{2β} b$. We show that global regular solutions in the cases $0 3$.
Keywords: Logarithmically supercritical; MHD system; Global regularity.